UPAYA MEMPERBAIKI MISKONSEPSI DAN HASIL BELAJAR SISWA KELAS XI-IPA1 SMAN 2 BAU-BAU MELALUI PENERAPAN MODEL PEMBELAJARAN ICI (INTERACTIVE CONCEPTUAL INSTRUCTION) BERBANTUAN LKS BERBASIS LINGKUNGAN - Ummi Salamah (Indonesian Journal Of Educational Research and Review, 2020)
An understanding of nature and the environment is one of the initial capital to meet future life, which all depend on the findings and breakthroughs in science and technology. This study aims to improve the misconceptions and physics learning outcomes of class XI-IPA students through the application of an environment-based worksheet based ICI learning. This type of research is Classroom Action Research. Implementation study consisted of two cycles of cycle one and cycle 2 with stages in each cycle of planning, action, observation, evaluation, and reflection. The research subjects were students of class XI-IPA Senior High School of  2 Bau-Bau with a total of 35 students. Research instruments and data collection techniques consisted of misconception tests, learning outcomes tests, psychomotor observation sheets, and affective observation sheets—data analysis technique using descriptive analysis of quantitative and qualitative consisting of completeness in classical analysis. The study showed that an increase in the learning outcomes of cycle one and cycle 2 in terms of cognitive, affective, and psychomotor. While on a review of misconceptions changes from cycle 1 to cycle 2. So it can be said that  ICI model can reduce student misconceptions and can improve student learning outcomes.